The Use of Know-Want-Learn Strategy to Teach Reading of Report Text to the Ninth Graders of SMPN 2 Sampang (RETAIN, 2017)
The Use of Know-Want-Learn Strategy to Teach Reading of Report Text to the Ninth Graders of SMPN 2 Sampang Yuliana Tri Utami English Education, Faculty of Languages and Arts, State University of Surabaya yulianautami@mhs.unesa.ac.id Dr. H. Aswandi, M.Pd. English Education, Faculty of Languages and Arts, State University of Surabaya aswandi@unesa.ac.id Abstrak Penelitian ini menyampaikan tentang sebuah strategi baru yang dapat digunakan oleh guru untuk membantu siswa yang kesulitan dalam memahami teks yang mereka baca. Strategi ini adalah strategi Know-Want-Learn (KWL) yang disarankan kepada siswa kelas sembilan SMPN 2 Sampang sebagai strategi membaca mereka dalam mempelajari bahasa Inggris. Membaca adalah kemampuan pertama yang sangat penting untuk dikuasai karena akan dapat membantu siswa memperoleh berbagai informasi khususnya dalam menguasai sebuah bahasa. Tujuan dari penelitian ini adalah bagaimana guru sebagai pengajar dapat mengurangi kesulitan siswa dalam membaca. Salah satu caranya adalah menyediakan pengajaran yang efektif dengan menggunakan strategi yang tepat. Strategi KWL dipilih untuk mengatasi permasalahan ini melalui tiga langkah dasar kognitif yaitu; menghubungkan apa yang siswa ketahui, menentukan apa yang siswa ingin pelajari, dan mengingat apa yang sudah dipelajari. Strategi KWL juga membantu siswa mengembangkan keingintahuan mereka terhadap materi yang dipelajari dan mempersiapkan berbagai pertanyaan sebelum, selama, dan setelah membaca untuk mengaitkannya dengan materi. Peneliti menggunakan penelitian kualitatif untuk memperoleh pengertian lebih dalam tentang studi ini.Data telah diperoleh melalui hasil pengamatan checklist dan field notes di kelas selama empat pertemuan. Studi ini menghasilkan dua hal. Pertama, guru telah meyelesaikan proses belajar mengajar melalui tiga langkah dasar kognitif dari pelaksanaan KWL dan sesuai dengan rencana pembelajaran. Kedua, siswa menunjukkan respon yang baik. Mereka dapat mengembangkan pemahaman mereka terhadap teks dengan menunjukkan inisiatif yang besar. Kata Kunci: Strategi KWL, Pemahaman Membaca, Teks Report Abstract This study presented about the new strategy that can be used by the teacher to help the students who have difficulties in comprehending the text they read. It was Know-Want-Learn (KWL) strategy which is proposed for the ninth graders of SMPN 2 Sampang as their reading strategy in learning English. Reading becomes the first skill that is crucial to be mastered because it assists the students achieve most of information. Student who has a good skill in reading will be easier to gain new knowledge, especially for language acquisition.The aim of this study is how the teacher as the instructor minimizes the students’ reading difficulties. One of the ways is by providing effective instruction using an appropriate strategy. KWL Strategy is chosen to solve this problem through three basic cognitive steps which are; accessing what the students Know, determining what the students Want to learn, and recalling what the students did Learn. It also helps the students develop their curiosity on the material and organize their inquiries before, during and after reading to connect with their learning. The researcher adopted a qualitative research to gain in-depth understanding about this study. The data was taken through the observation checklist and field notes in classroom for four meetings. This study results two things. The first, the teacher is carried out the learning process through three basic cognitive steps of KWL implementation and accordance with the lesson plan. The second, the students showed good responses. They could develop their understanding of the texts by showing great initiative. Keywords:The KWL Strategy, Reading Comprehension, Report Text